Physicochemical and rheological properties of foam mat dried pineapple Ananas comosus powders - Shaari, Nur Atiqah (2018)
Pineapple fruit (Ananas comosus) has a high moisture content and highly perishable. Pineapple fruit has a high sugar content, fibre, sticky, viscous and sensitive to heat which is quite unsuitable for drying methods such as spray drying and drum drying. Foam mat drying is a suitable method for dehydration of any heat sensitive, sticky and viscous materials. The aim of this study was to evaluate the foam properties using different foaming agents at different concentration and whipping time and compare the physicochemical properties of foam mat dried and spray dried pineapple powders. Pineapple juice was foamed using two different protein bases; egg albumen (5, 10, 20% w/w) and fish gelatin (5, 10, 20% w/w) and carbohydrate base; methylcellulose (0.5, 1.0, 1.5% w/w). Then, 5% w/w maltodextrin was added as a foam stabilizer. The mixtures were blended at different whipping time (10, 20 and 30 min) and foam pineapple juice was hot air-dried using cabinet dryer at 50 oC until reached moisture content less than 8% w.b. The dried foam mat was scratched, grinded and analyzed. The results showed that an increase in foaming agent (egg albumen and fish gelatin) concentration significantly increased the foam expansion and significantly decreased foam density (p ≤ 0.05). Analysis of physicochemical properties (pH, total soluble solid, acidity, water activity, moisture content, total phenolic content, color, water solubility index, water absorption index, bulk density and hygroscopicity) and rheological properties (steady shear and dynamic shear) were done on the reconstituted foam mat dried pineapple powder samples. The effect of temperature and concentration on rheological behavior of spray dried and foam mat dried pineapple juice concentrates were investigated using a rheometer over a wide range of temperatures (25-75 oC) and concentrations (10-50 oBrix). The pineapple juice concentrates fitted to the Power law model and exhibited shear thinning behavior within the range 0.01 < n <0.86. Consistency coefficient (K) and apparent viscosity of all samples increased as the concentration increased and temperature decreased. The activation energy of spray dried and foam mat dried pineapple juice concentrates treated with egg albumen and fish gelatin were found in the range of 19.96–49.56 kJ/mol, 11.67-36.30 kJ/mol and 12.36-23.66 kJ/mol, respectively. Foam mat dried pineapple juice treated with methylcellulose showed the highest G' (solid like) and G" (liquid like) values at all concentration (10-50 oBrix), followed by samples treated with egg albumen and fish gelatin. Foam mat dried pineapple juices treated with methylcellulose showed lower tan ẟ which represent concentrated samples followed by foam mat dried pineapple juices treated with egg albumen and fish gelatin. Foam mat dried pineapple powder is suitable for instant beverages and confectionery products like pie filling while spray dried pineapple powder recommended for instant beverages. The obtained data are useful in the food product development and the use of fish gelatin in this study could help in halal product development by replacing the use of mammalian gelatin since it has similar properties.